Gelatin-containing porous polycaprolactone PolyHIPEs as substrates for 3D breast cancer cell culture and vascular infiltration - Jackson, Caitlin E.; Doyle, Iona; Khan, Hamood; Williams, Samuel F.; Aldemir Dikici, Betül; Barajas Ledesma, Edgar; Bryant, Helen E.; English, William R.; Green, Nicola H.; Claeyssens, Frederik (Frontiers in Bioengineering and Biotechnology, 2024)
Tumour survival and growth are reliant on angiogenesis, the formation of new blood vessels, to facilitate nutrient and waste exchange and, importantly, provide a route for metastasis from a primary to a secondary site. Whilst current models can ensure the transport and exchange of nutrients and waste via diffusion over distances greater than 200 μm, many lack sufficient vasculature capable of recapitulating the tumour microenvironment and, thus, metastasis. In this study, we utilise gelatin-containing polymerised high internal phase emulsion (polyHIPE) templated polycaprolactone-methacrylate (PCL-M) scaffolds to fabricate a composite material to support the 3D culture of MDA-MB-231 breast cancer cells and vascular ingrowth. Firstly, we investigated the effect of gelatin within the scaffolds on the mechanical and chemical properties using compression testing and FTIR spectroscopy, respectively. Initial in vitro assessment of cell metabolic activity and vascular endothelial growth factor expression demonstrated that gelatin-containing PCL-M polyHIPEs are capable of supporting 3D breast cancer cell growth. We then utilised the chick chorioallantoic membrane (CAM) assay to assess the angiogenic potential of cell-seeded gelatin-containing PCL-M polyHIPEs, and vascular ingrowth within cell-seeded, surfactant and gelatin-containing scaffolds was investigated via histological staining. Overall, our study proposes a promising composite material to fabricate a substrate to support the 3D culture of cancer cells and vascular ingrowth.